THE ALCÂNTARA AGREEMENT AND THE UNITED STATE’S COVERT DEVELOPMENTALISM - Bojikian, Neusa Maria Pereira; Mariano, Karina L. Pasquariello [UNESP]; Thomaz, Laís Forti (Universidade Federal da Bahia, 2022)
The concern with Brazil’s spatial sector is part of a wider debate on the promotion of economic development as a basis for better international insertion of the country. Based on a literature review and case study, the research verified that, historically, Brazilian governments have varied in their adherence to the economic ideology defended by the United States, without considering that this country has developmentalist elements, acting as an agent of transfer and diffusion of new technologies. The goal is to show that the Technology Safeguards Agreement is functional for the US government’s strategy to promote development with covert State participation. In turn, this tends to represent important limitations to implementing spatial policies in Brazil. We infer that the TSA is an instrument by which the US government seeks to mitigate the regulatory risks to which its companies are subjected and leverage the competitiveness of its industrial base.
L’ACCORD ALCANTÂRA ET LE DÉVELOPPEMENTISME DISSIMULÉ DES ÉTATSUNIS
O ACORDO DE ALCÂNTARA E O DESENVOLVIMENTISMO OCULTO DOS ESTADOS UNIDOS
Keywords: Developmentalism; Neoliberalism; Relations between Brazil and the United States; Technology Safeguards Agreement (TSA)